2014
DOI: 10.1111/bph.12945
|View full text |Cite
|
Sign up to set email alerts
|

Targeting the cis‐dimerization of LINGO‐1 with low MW compounds affects its downstream signalling

Abstract: BACKGROUND AND PURPOSEThe transmembrane protein LINGO-1 is a negative regulator in the nervous system mainly affecting axonal regeneration, neuronal survival, oligodendrocyte differentiation and myelination. However, the molecular mechanisms regulating its functions are poorly understood. In the present study, we investigated the formation and the role of LINGO-1 cis-dimers in the regulation of its biological activity. EXPERIMENTAL APPROACHLINGO-1 homodimers were identified in both HEK293 and SH-SY5Y cells usi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
24
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(27 citation statements)
references
References 67 publications
1
24
0
Order By: Relevance
“…Therefore, TrkB receptor is supposed to be a critical component of multistep tumor progression. Additionally, our results support that the expression of LINGO-1 was increased after PHEN induction, accompanied with inhibition on the expression of TrkB and phosphorylated-TrkB [11]. Therefore, we hypothesize that the key tumorigenic signaling pathway involved in PHEN may include TrkB receptor activation followed by the Akt cascade, which relates with TrkB phosphorylation and the enhanced resistance against apoptosis.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…Therefore, TrkB receptor is supposed to be a critical component of multistep tumor progression. Additionally, our results support that the expression of LINGO-1 was increased after PHEN induction, accompanied with inhibition on the expression of TrkB and phosphorylated-TrkB [11]. Therefore, we hypothesize that the key tumorigenic signaling pathway involved in PHEN may include TrkB receptor activation followed by the Akt cascade, which relates with TrkB phosphorylation and the enhanced resistance against apoptosis.…”
Section: Discussionsupporting
confidence: 80%
“…Recently, Cobret et al found that PHEN was able to increase the function of LINGO-1 [11]. LINGO-1 is reported to be a key component of the Nogo receptor complex whose ingredients also include Nogo-A receptor (NgR1) and p75 neurotrophin receptor (p75NTR)/tumor necrosis factor receptor superfamily 19(TROY) [12].…”
Section: Discussionmentioning
confidence: 99%
“…Despite the identification of numerous APP-interacting proteins, the quest for the discovery of credible ligand(s) for putative APP receptor remains unfulfilled (see Outstanding Questions). On the other hand, it is plausible that the APP ectodomain itself might serve as a ligand for APP and possibly other receptors as it has been proposed for lingo-1 [78, 79] . In all, cell surface recycling of putative APP receptor, either through endocytic trafficking, glycosylation, ubiquitination or kinase-dependent processes, would modulate Aβ production.…”
Section: Discussionmentioning
confidence: 99%
“…This structural feature may enable membrane-tethered APP to interact directly with soluble APP ectodomain (or the ectodomains of APP homologues) [60, 65] . As reported for lingo-1, a type-1 transmembrane protein, APP could function both as a ligand and a receptor through trans self-dimerization [78, 79] . Indeed, it has been shown that the disulfide bond in the E1 domain might be the main contributor for trans-dimerization between APP molecules and its homologues [34, 58, 59, 72] , although the E2 domain could still account partially to enhance synaptic connections in the absence of E1 [77] .…”
Section: The Role Of App Subdomains In Dimerization Processmentioning
confidence: 99%
“…Furthermore, when myelin is damaged, endogenous myelin proteins, as well as axonal proteins, are exposed and can also contribute to impaired remyelination. One such protein is LINGO-1, an inhibitor of OPC differentiation that is expressed in myelin and in neurons (Cobret et al, 2015;Emery, 2010;Jepson et al, 2012;Lee, Shao, Sheng, Pepinsky, & Mi, 2014;Ranger et al, 2018). Both shRNA knockdown and pharmacological blockade of LINGO-1 are effective at promoting functional EAE recovery and remyelination in vivo (Mi et al, 2007;Wang et al, 2014;Yin & Hu, 2014).…”
Section: Impact Of Glial Proteins On Remyelinationmentioning
confidence: 99%